Languages and Worldview - Allard-Kropp, Manon; Open Textbook Library (Open Textbook Library, 2020)
Asking and answering questions about what culture entails and examines the fundamental properties and intertwining nature of language and culture. This text explores linguistic relativity, lexical differences among languages and intercultural communication, including high and low contexts. Changes to a variety of OER works were made by Manon Allard-Kropp in the Department of Language and Cultural Studies to tailor the text to fit the needs of the Languages and World View course at the University of Missouri-St. Louis. Materials from the original sources have been combined, reorganized, and added to by the current author, and any conceptual or typographical errors are the responsibility of the current author.
PART 1 Language and Culture: Concepts and Definitions -- PART 2 Conveying Meaning -- PART 3 The Ethnolinguistic Perspective -- PART 4 Language, Worldviews, and Intercultural Communication -- ADDENDUM
In English.
Description based on online resource
Keywords: Humanities -- Textbooks; Linguistics -- Textbooks; Social sciences -- Textbooks; Anthropology -- Textbooks